A randomized controlled trial comparing nonoxynol-9 lubricated condoms with silicone lubricated condoms for prophylaxis. Issue 2 (April 1998) - Roddy, R E; Cordero, M; Ryan, K A; Figueroa, J
Abstract : OBJECTIVE: We tested the effect of nonoxynol-9 (N-9) in condom lubrication on the risk of acquiring STD and genital discomfort. METHODS: The study was a triple masked, randomised controlled trial comparing N-9 lubricated condoms with plain silicone lubricated condoms among Dominican female sex workers. RESULTS: Randomisation provided two groups (313 for N-9 and 322 for plain) similar in baseline characteristics, but extensive loss to follow up occurred (56 women in each group completed the 24 week follow up). Most vaginal acts with clients were protected with condoms (99% of vaginal sex) but fewer acts with non-clients were protected (43% of vaginal sex). No significant differences occurred in rates of cervical infections (N-9 = 3.4 per 100 person months v plain = 2.8), trichomoniasis (N-9 = 2.8 v plain = 3.6), or discomfort rates (N-9 = 0.82 v plain = 0.92). CONCLUSIONS: Plain silicone lubricated condoms are as effective as N-9 lubricated condoms, cost less, have longer expected shelf life, and therefore may be the better condom to provide.